Eligibility criteria for therapeutic hypothermia: From trials to clinical practice. (4th October 2016) - Mehta, Shailender; Joshi, Anjali; Bajuk, Barbara; Badawi, Nadia; McIntyre, Sarah; Lui, Kei
Abstract : Aim: Whole body therapeutic hypothermia (TH) for hypoxic ischaemic encephalopathy was introduced into clinical practice in New South Wales (NSW) and Australian Capital Territory in 2007. State‐wide policy adopting the eligibility criteria and practice based on trial‐designs was published in 2009. Methods: The study was conducted by retrospectively reviewing medical records of all TH infants born between 2007 and 2011 in NSW and Australian Capital Territory to examine if eligibility criteria (assessed against evidence‐based policy directives) were met. Results: A total of 207 infants received TH, 104 (50%) did not meet the eligibility criteria defined in NSW policy directive. Over the 5‐year period, the proportion of infants meeting the eligibility criteria did not change. Seventy percent of infants (73 out of 104) not meeting eligibility criteria did not fulfil the criteria for 'evidence of asphyxia', although half of them met 'moderate or severe encephalopathy criterion'. Adverse events (hypotension, coagulopathy and arrhythmia), were more common in the 'criteria met' group than the 'criteria not met' group (89 vs. 71%, P = 0.001). Similar proportions of infants had TH discontinued before 72 h (criteria met: 32 (31%) vs. criteria not met: 27(26%)). Most frequent reason for early cessation was 'palliation' (19/32, 59%) in criteria met and 'clinical improvement' (16/27, 59%) in criteria not met group. Conclusions: Many TH infants were treated based on clinician judgement, though not meeting the trial‐design policy criteria. Early TH cessation (<72 h) was common. Future studies are warranted on long‐term neurodevelopmental outcomes for all infants receiving TH particularly those with early cessation of therapy.